Correctness of multi-dimensional Darboux problems for the wave equation - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
It is proved that multi-dimensional Darboux problems for the wave equation are correct in the domain \(D_3 E_m + 1 \) bounded by the surfaces ¦x ¦=t + ɛ and ¦x ¦=1- t and the plane t = 0, 0 ≤ ɛ < 1. The behavior of the solutions as ɛ → 0 is studied.